2018
DOI: 10.1080/17461391.2018.1469674
|View full text |Cite
|
Sign up to set email alerts
|

Greater fatigability in knee‐flexors vs. knee‐extensors after a standardized fatiguing protocol

Abstract: The present study aimed to investigate the effects of a standardized fatiguing protocol on central and peripheral fatigue in knee-flexors and knee-extensors. Thirteen healthy men (age: 23 ± 3 years; height: 1.78 ± 0.09 m; body-mass: 73.6 ± 9.2 kg) volunteered for the present study. Maximal voluntary contraction (MVC), Electromyography (EMG) activity, voluntary activation level (VAL) as an index of central fatigue and twitch potentiation as an index of peripheral fatigue were measured before and after the fatig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
(99 reference statements)
0
11
2
Order By: Relevance
“…The voluntary activation level was calculated using the interpolated twitch technique. At baseline, the interpolated twitch technique was performed eliciting a superimposed doublet with an interpulse duration of 10 ms (100 Hz) (2,22). During this procedure, a stimulating electrode (24 Â 24 mm circle electrode; Spes Medica, Battipaglia (SA), Italy) was positioned above the femoral nerve under the iliopubic ligament, whereas the receiving electrode (40 Â 90 mm rectangular electrode; Spes Medica) was placed 2 cm under the superior posterior iliac spine.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The voluntary activation level was calculated using the interpolated twitch technique. At baseline, the interpolated twitch technique was performed eliciting a superimposed doublet with an interpulse duration of 10 ms (100 Hz) (2,22). During this procedure, a stimulating electrode (24 Â 24 mm circle electrode; Spes Medica, Battipaglia (SA), Italy) was positioned above the femoral nerve under the iliopubic ligament, whereas the receiving electrode (40 Â 90 mm rectangular electrode; Spes Medica) was placed 2 cm under the superior posterior iliac spine.…”
Section: Measurementsmentioning
confidence: 99%
“…The neuromuscular factors involved in the force-generating capacity can be further divided into central or peripheral by using the interpolated twitch technique (21). Indeed, through electrical stimulations, it is possible to calculate the voluntary activation and the peak force (pF) recorded after a maximal voluntary contraction as central or peripheral factor, respectively (22). In SM, the central contribution has been identified as a prevalent neuromuscular factor affecting the forcegenerating capacity (8).…”
mentioning
confidence: 99%
“…Besides exercise performance, it has been proposed that there is a high probability of muscle injuries (non-contact injuries) after HT (Rahnama et al, 2002) due to decreased muscle temperature during HT (Woods and Bishop, 2007) and from muscle strength deficiency before the commencement of the second half (Yamamoto, 1993;Rahnama et al, 2002). Previous studies have also reported that knee flexors are more fatigable (increased peak joint torque angle and electromyogram activity) than knee extensors and have been associated with hamstring muscle injuries (Coratella et al, 2015(Coratella et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…SM-2000N, Interface, Crowthorne, UK). The participants sat on the chair at a hip angle of 80° (0°=full extension) and were secured by two seatbelts 18 . The belts secured the tested limb at 90° of knee flexion (0°=full extension) as used in previous relevant procedures 12 and the untested limb was immobilized by a fixed lever 17 .…”
mentioning
confidence: 99%
“…Before the maximal voluntary contraction assessment, the participants were familiarized with the procedures. Thereafter, they performed a warm-up protocol consisting of 20 1-s to 2-s isometric contractions, separated by 10 s each, starting from a self-selected force and progressively increasing until the maximal volitional force was exerted 18 . After five minutes, the participants were asked if they were ready to start and in case of negative response, more time to recover was provided.…”
mentioning
confidence: 99%